The Influence of Service Features and Technology Acceptance in BSI Mobile Banking on Customer Loyalty: The Mediating Role of Satisfaction - Meisya Rizki Aurelia; Nilam Anggar Sari; Setiati Setiati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of service features and technology acceptance on customer loyalty with satisfaction as a mediating variable among BSI mobile banking users at Kutai Kartanegara University. The research approach used a descriptive quantitative method with 190 respondents obtained through accidental sampling using a 1–5 point Likert scale. Data analysis was performed using SmartPLS software version 4.1.1.6. Customer satisfaction was found to be positively and significantly affected by service features, perceived ease of use, and perceived usefulness. However, perceived ease of use and perceived usefulness do not directly affect customer loyalty, but are mediated by satisfaction. These findings confirm that satisfaction is a key factor that bridges the influence of service features and technology acceptance on customer loyalty. Therefore, improving the quality of digital features and optimizing the benefits of technology need to be directed at strengthening satisfaction in order to create sustainable loyalty to the use of BSI mobile banking.